The effect of neoadjuvant chemotherapy among patients undergoing radical cystectomy for variant histology bladder cancer: A systematic review. Issue 1 (2nd January 2022) - Alvarez-Maestro, Mario; Chierigo, Francesco; Mantica, Guglielmo; Quesada-Olarte, J. M.; Carrion, D. M.; Gomez-Rivas, Juan; Pinto-Marin, Alvaro; Aguilera Bazan, Alfredo; Martinez-Piñeiro, Luis
ABSTRACT: Objective: To systematically review the evidence about the effect of neoadjuvant chemotherapy (NAC) for muscle-invasive bladder cancer (MIBC) with pure urothelial carcinoma (pUC) in radical cystectomy (RC) candidates affected by variant histology (VH) bladder cancer. Methods: A review of the current literature was conducted through the Medline and National Center for Biotechnology Information (NCBI) PubMed, Scopus databases in May 2020. The updated Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed for this systematic review. Keywords used were 'bladder cancer', 'bladder carcinoma', 'bladder tumour' and 'bladder cancer variants' and 'neoadjuvant chemotherapy'. Only original articles in English published after 2000 and reporting oncological outcomes a series of more than five patients with VH were included. We excluded series in which the oncological outcomes of patients with pUC and VH were undistinguishable. Results: The literature search identified 2231 articles. A total of 51 full-text articles were assessed for eligibility, with 17 eventually considered for systematic review, for a cohort of 450, 367 patients, of which 5010 underwent NAC + RC. The median age at initial diagnosis ranged from 61 to 71 years. Most patients received cisplatin-gemcitabine, methotrexate-vinblastine-adriamycin-cisplatin, or carboplatin-based chemotherapy. Only one study reported results of neoadjuvant immunotherapy. The median follow-up ranged from 1 to 120 months. The results showed that squamous cell carcinoma (SCC) is less sensitive to NAC than pUC and that SCC predicts poorer prognosis. NAC was found to be a valid approach in treating small cell carcinoma and may have potential benefit in micropapillary carcinoma. Conclusions: NAC showed the best oncological outcomes in small cell variants and micropapillary carcinoma, while NAC survival benefit for SCC and adenocarcinoma variants needs further studies. Drawing definite considerations on the efficacy of NAC in VH is complicated due to the heterogeneity of present literature. Present results need to be confirmed in randomised controlled trials.